2008
DOI: 10.2139/ssrn.1069862
|View full text |Cite
|
Sign up to set email alerts
|

Commodities and Equities: 'A Market of One'?

Abstract: Amidst a sharp rise in commodity investing, many have asked whether commodities nowadays move in sync with traditional financial assets. We provide evidence that challenges this idea. Using dynamic correlation and recursive cointegration techniques, we find that the relation between the returns on investable commodity and U.S. equity indices has not changed significantly in the last fifteen years. We also find no evidence of any secular increase in co-movement between the returns on commodity and equity invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
73
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 28 publications
13
73
1
2
Order By: Relevance
“…2 Also, returns of stocks−measured by SP500−and commodities became more correlated. Finally, as mentioned in Basak and Pavlova (2014), related empirical literature dates the start of the financialization of commodity futures around 2004 (see Buyuksahin et al, 2008;Irwin & Sanders, 2011;Tang & Xiong, 2012;Hamilton & Wu, 2013;Boons, de Roon & Szymanowska, 2014, among others), with some works explicitly testing for and confirming a structural break around 2004.…”
Section: Empirical Analysis: Data and Model Specificationmentioning
confidence: 99%
“…2 Also, returns of stocks−measured by SP500−and commodities became more correlated. Finally, as mentioned in Basak and Pavlova (2014), related empirical literature dates the start of the financialization of commodity futures around 2004 (see Buyuksahin et al, 2008;Irwin & Sanders, 2011;Tang & Xiong, 2012;Hamilton & Wu, 2013;Boons, de Roon & Szymanowska, 2014, among others), with some works explicitly testing for and confirming a structural break around 2004.…”
Section: Empirical Analysis: Data and Model Specificationmentioning
confidence: 99%
“…1 The effects of a broader participation of financial operators on the interdependence among the futures prices of different asset classes (e.g. oil prices, other commodity prices and stock prices) are studied empirically by several researchers (among others, Büyükşahin et al [6], Büyükşahin et al [7], Büyükşahin and Harris [4], Tang and Xiong [36], Büyükşahin and Robe [5] and Silvennoinen and Thorp [33]). 2 According to Büyükşahin et al [6] market participation by hedge funds and commodity index traders had surged since 2002.…”
Section: On the Financialization Of Crude Oil Marketsmentioning
confidence: 99%
“…In contrast, economists from the Commodity Futures Trading Commission (CFCT) which is the American supervisory agency used data from American markets until May 2008 and concluded that there has been no recent loss of independence of equity and commodity markets and the attraction of commodity markets for asset diversification has not been diminished [3].…”
Section: Increasing Relationship Between Commodity Market and Equity mentioning
confidence: 99%
“…That is to say, although the commodity market becomes to assume a character of a financial market, the attraction for portfolio diversification has not been lost 3 . However, after July 2008, and particularly after the Lehman shock in September of the same year, the markets have taken on a completely different appearance.…”
Section: Increasing Relationship Between Commodity Market and Equity mentioning
confidence: 99%